IDENTIFIKASI PERILAKU CALON MAHASISWA BARU DALAM MEMILIH PROGRAM STUDI MENGGUNAKAN ANALISIS FAKTOR - Maxsi Ari (LPPM Universitas Bina Sarana Informatika, 2014)
Private universities is one alternative for the community colleges to meet increased demand for educational needs. The number of private colleges, especially in London and generally in Indonesia is quite a lot. The number of colleges and universities means used to attract prospective students an interesting thing to study. As a reason for the intense competition in the search for new students, no doubt there are some ways that actually do not need to be done. Issues raised were identifying what the underlying prospective students in choosing courses or majors using factor analysis. Data obtained from the questionnaire prospective new students in February 2014.SPSS is use for processing the data. The results of factor analysis to establish a correlation matrix form, choose the method of factor analysis, and determine the number of factors. The results of the factor analysis measurement of identifying new prospective students in choosing courses or majors are strategy factor and image factor.